(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2025)
Diabetes is a global health challenge, with oxidative stress playing a crucial role in its development. Incorporating functional foods derived from medicinal plants is an effective approach to diabetes management. This study aimed to formulate and evaluate a composite herbal tea using Clitoria ternatea (Bluepea) as the primary ingredient, combined with Mentha arvensis (Mint), Cymbopogon citratus (Lemongrass), and Rosa centifolia (Rose petals) known for their pharmacological properties. Three herbal tea formulations were developed and subjected to sensory analysis to select the most acceptable formulation, which was then subjected to proximate nutrient analysis, phytochemical analysis, DPPH assay, microbial analysis, and in vitro α-amylase inhibitory activity. Statistical analysis was performed using SPSS version 26. Blue pea and lemongrass formulation was the most acceptable formulation, with one-way ANOVA results reporting statistically significant differences (P <0.001). Nutrient analysis showed low moisture content (2.95%) with a product acceptability index of 91.60%. It also exhibited a strong antioxidant activity with an IC50 value of 0.385 µg/g and demonstrated dose-dependent in vitro α-amylase inhibitory activity, indicating the potential for glycemic control. Microbial analysis confirmed the product’s safety for consumption. The composite herbal tea is a promising functional beverage for diabetes management, with potent antioxidant properties and alpha-amylase inhibitory activity.